2013
DOI: 10.1002/esp.3499
|View full text |Cite
|
Sign up to set email alerts
|

Bedload transport measurements with impact plate geophones: comparison of sensor calibration in different gravel‐bed streams

Abstract: Indirect bedload transport measurements have been made with the Swiss plate geophone system in five gravel‐bed mountain streams. These geophone sensors record the motion of bedload particles transported over a steel plate mounted flush with the channel bed. To calibrate the geophone system, direct bedload transport measurements were undertaken simultaneously. At the Erlenbach in Switzerland, a moving‐basket sampler was used. At the Fischbach and Ruetz streams in Austria, a Helley–Smith type bedload sampler pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
204
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 120 publications
(218 citation statements)
references
References 34 publications
12
204
0
2
Order By: Relevance
“…To measure the energy delivered by an impact, we used a Swiss plate geophone system sensor unit (Figure 1), which is a sensor system developed for the field monitoring of bedload transport (Rickenmann, Turowski, Fritschi, Klaiber, & Ludwig, 2012;Rickenmann et al, 2014;Turowski, Böckli, Rickenmann, & Beer, 2013;Turowski & Rickenmann, 2011;Turowski, Yager, Badoux, Rickenmann, & Molnar, 2009). The sensor unit contains a geophone fixed in the centre under a steel plate with the dimensions 360 × 500 × 6 mm.…”
Section: Methodsmentioning
confidence: 99%
“…To measure the energy delivered by an impact, we used a Swiss plate geophone system sensor unit (Figure 1), which is a sensor system developed for the field monitoring of bedload transport (Rickenmann, Turowski, Fritschi, Klaiber, & Ludwig, 2012;Rickenmann et al, 2014;Turowski, Böckli, Rickenmann, & Beer, 2013;Turowski & Rickenmann, 2011;Turowski, Yager, Badoux, Rickenmann, & Molnar, 2009). The sensor unit contains a geophone fixed in the centre under a steel plate with the dimensions 360 × 500 × 6 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Using the so-called amplitude histograms (AHs), Wyss et al (2016Wyss et al ( , 2014 demonstrated for the SPG measurements at the Erlenbach (Swiss Prealps) that absolute bedload masses for each grain size class could be successfully calculated for both the calibration and validation data obtained with the moving basket samplers. The continuous recording of AH data was also implemented at the Fischbach and Ruetz measuring sites, with a recording interval of 1 min.…”
Section: Signal Pre-processing Recorded Geophone Values and Amplitumentioning
confidence: 99%
“…Recorded signals contain information on both sediment impact rate and bedload particle sizes. One of the most widely used techniques consists in recording the signal of particle impacts on steel objects like plates (Rickenmann et al, 2014;Wyss et al, 2016a), pipes (Mao et al, 2016;Mizuyama et al, 2010) or column pipes (Papanicolaou et al, 2009). Other passive instruments consist in directly recording bedload SGN by using passive acoustic monitoring (PAM) (Barton, 2006;Bedeus and Ivicsis, 1963;Geay, 2013;Geay et al, 2017a;Thorne, 1986a, b) or seismic monitoring (Gimbert et al, 2014;Roth et al, 2016;Tsai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other passive instruments consist in directly recording bedload SGN by using passive acoustic monitoring (PAM) (Barton, 2006;Bedeus and Ivicsis, 1963;Geay, 2013;Geay et al, 2017a;Thorne, 1986a, b) or seismic monitoring (Gimbert et al, 2014;Roth et al, 2016;Tsai et al, 2012). Measuring bedload GSD with passive methods has been achieved using plates (Barrière et al, 2015;Krein et al, 2014;Rickenmann et al, 2014;Wyss et al, 2016b) or pipes (Dell'Agnese et al, 2014;Mizuyama et al, 2010;Papanicolaou et al, 2009), and SGN (Geay et al, 2017a;Johnson and Muir, 1969;Jonys, 1976;Thorne, 1986a, b), by using experimental laws of calibration. Concerning seismic methods, bedload GSD measurements were not yet proposed as a direct application.…”
Section: Introductionmentioning
confidence: 99%